A terceira margem : uma análise do cotidiano da população em situação de rua - Jesus Alexandre Tavares Monteiro (2011)
This paper aims to understand the everyday life of the homeless population from the city of Belo Horizonte. Through the gathering of life stories, participative research and literature review we went into the street procedures, and through literary passages, musical compositions and images we present this paper as a background to the discussions of the subjectivity of homeless surviving. This paper’s purpose is to understand what are the street rules and the ways in which this public reinvents themselves in everyday life. This research is justified by the constantly increasing of the population in Brazilian municipalities, according to the last population census from Minister of Social Development – MDS (2008) it’s quantified in 31.992 people over 18 years old in 71 municipalities (with the population over 300.000 inhabitants). We built a theoretic reflection to guide us against the infinity of intermittent and renewable actions that is the everyday life of the homeless population. Through a conceptual basis came from Ergology, more specifically from the thoughts of the ergologist philosopher Yves Schwartz and from the conceptual perspective of the daily from the historian Michel Certeau. The choice to present the everyday life from the homeless population divided in periods of the Day – morning, afternoon, night and dawn – came from the didactic proposal to ease the infinity of confluences that permeates the streets, and also as an answer to the constantly invitation from the interviewed to go out and see the streets in its entirety along with the ones that make it as their own home. Therefore, this paper is about the daily of the homeless population and its way to survive and reinvent the daily.